KEARIFAN LOKAL DALAM PENGELOLAAN SUMBERDAYA ALAM HUTAN DAN EKOSISTEM (SDHAE) PADA MASYARAKAT DESA PENYANGGA TAMAN NASIONAL MERU BETIRI - Diah Puspaningrum (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2015)
This research aims to dig the potentials of each areas based on their local wisdom (resources, knowledge, culture and process) in the areas of villagers of buffer villages at Meru Betiri National Park. The research uses qualitative approach and purposive random sampling is used to determine research location. The locations chosen are buffer villages within the area of Meru Betiri National Park. The activity is conducted in all section of Meru Betiri National Park: Area Section I Sorongan (Rajegwesi), Area Section II Sorongan (Rajegwesi), Area Section II Ambulu (Curahnongko) and Area Section III Kalibaru (Kebunrejo). Data collection is conducted through rapid appraisal methods. The methods used in the researchs consisted of: indepth interview, field observation, and FGD (focus discussion group) thus various data collection technique are used (triangulation technique). Data analysis method collected through indepth interview and observation is using interactive data analysis from Miles and Huberman (1992). The conclusion of the research is that local wisdom owned by villagers of buffer villages in terms of local culture is varied. It is especially indicated in their value system of local culture. The local knowledge is relatively good in which there are technological use adjusted with the management of natural result. Local process in terms of gotong royong (mutual cooperation) and discussion still exists; however, it needs to be maintained for the sustainability of SDAHE management at Meru Betiri National Park. The potential of local resources owned by each buffer villages is different from each other.Keywords: Local wisdom, Natural Resources of Forest and Ecosystem (SDHAE), Buffer Village, Meru Betiri National Park